Soldiers' Work; Soldiers' Health: Morbidity, Mortality, and their Causes in an 1840s British Garrison in Canada - Duffin, Jacalyn (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1996)
The Port Wellington Hospital Register contains the case histories of 278 soldiers treated by military physicians in an 1840s British garrison. A computer-assisted analysis of the register provides information about illnesses suffered and the treatments prescribed, and allows for an examination of both soldiers and their doctors as workers. The soldiers were often ill because of the working conditions associated with soldiering, and their doctors were sometimes aware of the causal connection. This study leads to the epistemological suggestion that the disease labels used by the physicians were influenced by their working relationships with their solider-patients and their superiors in the military setting.